2018
DOI: 10.18775/ijmsba.1849-5664-5419.2014.46.1004
|View full text |Cite
|
Sign up to set email alerts
|

Employee Engagement and Factors that Influence: Experiences of Lecturers in Indonesia

Abstract: In this changing world, regarding global perspective and workforce changes, the involvement of employee is the most important feature for organization competitive. Employee engagement now is considered as a valuable indicator for organizational success, therefore, it needs to be studied in-depth by the organization, because through engaged employees the significant results can be achieved. Employee engagement has become a crucial issue in human resources management reviews, as it provides many benefits to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Employee engagement had a significant influence on employee turnover intentions. The results parallel the findings of numerous academics who contend that employees who are actively and consistently immersed in their work are so filled with positive energy that they have little time or room for negative thoughts, like quitting the organization (Ali et al, 2020;Cassim et al, 2024;Margaretha et al, 2018).…”
Section: Theoretical Implicationssupporting
confidence: 81%
“…Employee engagement had a significant influence on employee turnover intentions. The results parallel the findings of numerous academics who contend that employees who are actively and consistently immersed in their work are so filled with positive energy that they have little time or room for negative thoughts, like quitting the organization (Ali et al, 2020;Cassim et al, 2024;Margaretha et al, 2018).…”
Section: Theoretical Implicationssupporting
confidence: 81%
“…In a study conducted by Saks (2006), different meanings were found for work or job and organizational engagement. Also, EE is distinct from other organizational behavior concepts, such as job involvement, citizenship, and commitment (Margaretha et al, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
“…The results have presented a 5-factor model that positively affects employee engagement, ranked in descending order: Job characteristics, Colleagues relationship, School reputation, Salary and welfare, Organizational support. Margaretha et al, (2018) conducted a study on employee engagement and influencing factors in Indonesia. This study aimed to understand the factors that affect employee engagement of lecturers in Indonesia.…”
Section: Driven Factors Of Employee Engagementmentioning
confidence: 99%